Lubricating oil production waste gas adsorbent and preparation method thereof

By controlling the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole, ZIF-8MOF material was prepared, and fluorinated graphene and hydrophobic carbon dot HCDs were added, the problems of easy destruction of activated carbon structure and insufficient hydrophobicity in the prior art were solved, and efficient waste gas adsorption and recycling performance were achieved.

CN118719022BActive Publication Date: 2025-04-15JIANGSU NAKE LUBRICATION TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411032197.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-04-15
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

In the prior art, when processing lubricating oil to produce waste gas, the structure of activated carbon is easily damaged, the surface area is reduced, the service life is shortened, and the hydrophobicity is insufficient, it is easily disturbed by water vapor, and the adsorption efficiency is low.

Method used

ZIF-8MOF material was prepared by controlling the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole, using solvent hydrothermal method, and the hydrophobicity and adsorption properties of the material were enhanced by the addition of fluorinated graphene and hydrophobic carbon dot HCDs.

Benefits of technology

The high temperature resistance, hydrophobic properties and adsorption efficiency of the waste gas adsorbent were improved, the benzene adsorption rate reached 98.4%, the volatile alkane adsorption rate was 99.2%, and the adsorption capacity attenuation was only 3% after 100 cycles, which significantly improved the cyclic adsorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118719022B_ABST
    Figure CN118719022B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of separation and adsorption of waste gas from lubricating oil production, specifically to a waste gas adsorbent for lubricating oil production and a preparation method thereof. The waste gas adsorbent is prepared by immersing HFGO@ZIF‑8‑HCDs synthesized by a solvent thermal method from ZIF‑8 in an improver solution, and then separated and washed to prepare the synthesis. The present invention controls the molar ratio of raw materials, and obtains ZIF‑8 with low impurity content and good heat resistance by a solvent hydrothermal method; the present invention controls the source and molar ratio of raw materials by changing the solvent type, and the obtained ZIF‑8 has a high specific surface area; the present invention controls the fluorination degree and dosage of HFGO by adding fluorinated graphene, and the obtained HFGO@ZIF‑8 has good hydrophobic properties; the fluorinated graphene is dissolved by HCDs solution, and loaded in ZIF‑8 by a solvent thermal method, so as to obtain a waste gas adsorbent with good waste gas separation and adsorption performance; the present invention controls the concentration of an improver by adding the improver, and obtains a waste gas adsorbent with good cyclic adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of separation and adsorption of waste gas from lubricating oil production, and in particular to a lubricating oil production waste gas adsorbent and a preparation method thereof. Background Art

[0002] Lubricating oil is an important component of industrial lubricants. The lubricating oil industry has been developing continuously since its birth and has formed a series of rich varieties of lubricating products. In recent years, with the development of science and technology and industry, the use of mechanical equipment has become more extensive, and people's demand for new high-performance lubricating products has also increased. Therefore, the production of lubricating oil has gradually increased. In the process of lubricating oil production, a large number of volatile hydrocarbons will be produced, including alkanes, alkenes, cycloalkanes, aromatic hydrocarbons and other organic volatile compounds. These volatile organic compounds are harmful to the human body. Representative polycyclic aromatic hydrocarbons are also carcinogenic. At the same time, strong volatility has also become one of the main factors of environmental atmosphere and indoor air pollution. Therefore, the separation, detection and treatment of waste gas from lubricating oil production is of great practical significance for monitoring the degree of pollution in the atmosphere, protecting the environmental atmosphere and maintaining human health.

[0003] Various types of waste gas separation and filtration devices are used in industrial production to absorb and filter production waste gas. However, most waste gas filtration devices precipitate the internal impurities of the lubricating oil by adding various materials, and then filter it with a filter mesh. The filtration effect is slow and the usability is poor. Some other lubricating oil waste gas filtration devices cannot control the flow rate of the lubricating oil when filtering the lubricating oil. The large amount of impurities in the filtered water will cause the lubricating oil filtration speed to be slow. If the lubricating oil is input again, it will affect the filtration effect of the lubricating oil and the usability is poor. The lubricating oil production waste gas filtration equipment cannot selectively filter and adsorb waste gas and water molecules, resulting in poor applicability of the filtration device.

[0004] There are three types of organic waste gas treatment methods: non-destructive methods, destructive methods and biological treatment methods. Currently, the adsorption-desorption method is mainly used among the non-destructive methods to facilitate the recovery of oil and gas. The most important factor in the adsorption-desorption method is the adsorbent. Commonly used adsorbents include molecular sieves, activated carbon (granular) and activated carbon fiber, activated alumina, silica gel, etc.

[0005] Adsorption is one of the more commonly used separation and treatment technologies. For hydrocarbon volatile compounds, wood and coal-based activated carbon with mainly medium and micropores is used to regenerate the activated carbon through vacuum. However, when the activated carbon and regeneration method are used for separation and treatment of waste gas from lubricating oil production, because hydrocarbons are heavy, with large molecular weight and diameter, and the waste gas in the tank area contains moisture, conventional activated carbon has a strong hydrophilicity, resulting in a decrease in adsorption capacity, and the gaps are easily blocked, and vacuum desorption is impossible, which ultimately leads to rapid deactivation of the activated carbon.

[0006] Patent CN202010187049.8 reports a hydrophobic activated carbon adsorbent for treating high-humidity VOCs and a preparation method thereof. The hydrophobic activated carbon adsorbent is obtained by heating and activating the activated carbon and hydrophobically modifying it. The prepared activated carbon adsorbent has excellent hydrophobic properties and better adsorption effect on volatile waste gases in high-humidity environments. However, the limited surface area and surface roughness of the activated carbon adsorbent still limit its adsorption efficiency for waste gases, and the adsorption performance needs to be further improved.

[0007] Patent CN201410540567.8 reports a method for preparing a hydrophobic activated carbon modified material, wherein the activated carbon is prepared by liquid phase impregnation, filtration and drying of ethyl orthosilicate as an additive, hexadecyltrimethoxysilane as a modifier and anhydrous ethanol as a solvent; the modified activated carbon is hydrophobically modified by covering the surface of the activated carbon with various hydrophobic additives, but while the hydrophobic performance is improved, the specific surface area is also greatly reduced, and the adsorption performance drops sharply. At the same time, the hydrophobic groups covered on the surface further limit the desorption of the exhaust gas, reducing the service life of the adsorption material.

[0008] To sum up, with the increase of people's environmental awareness and the increasingly stringent laws, it is increasingly important to treat volatile waste gases generated in the production of lubricants, especially hydrocarbon volatile compounds and benzene series. However, due to the interference of environmental humidity, moisture, and process conditions in production, the use of mechanical devices to separate and adsorb the generated waste gases has poor applicability and cannot be desorbed and recovered; the effect of water molecules on the device limits the scope of use; in addition, adsorption materials are used for separation and treatment in the prior art, but the structure of activated carbon is easily destroyed during use, the specific surface area decreases, and the service life is shortened; the hydrophobicity is not enough and it is easily disturbed by water vapor during the adsorption process, reducing the adsorption efficiency; the sensitivity to high temperature and flammability make it impossible to reuse and there are safety hazards; inorganic material adsorbents have high polarity, and the waste gas generated by lubricating oil is mostly non-polar volatile compounds, and the adsorption efficiency is low.

[0009] Therefore, a lubricating oil production waste gas adsorbent and a preparation method thereof are proposed. Summary of the invention

[0010] The object of the present invention is to provide a lubricating oil production waste gas adsorbent and a preparation method thereof. By controlling the molar ratio of zinc nitrate hexahydrate and 2-methylimidazole, the yield of ZIF-8 prepared by solvent hydrothermal method is the highest, T 10% 428℃, T 50% 556℃, showing significantly improved high temperature resistance; zinc nitrate hexahydrate was used as Zn 2+ The average particle size of the prepared ZIF-8 precursor was 50 nm and the specific surface area was 1658 m 2 / g, the adsorption capacity is enhanced; the hydrophobicity of ZIF-8 is enhanced by using imidazole raw materials, and fluorinated graphene is added for synergistic effect. The water contact angle of the prepared HFGO@ZIF-8 material is 110.8°, which has significantly improved hydrophobic performance; the fluorinated graphene is dissolved in a solution prepared by hydrophobic carbon dots HCDs, and the concentration multiples of the HCDs solution are controlled to obtain a waste gas adsorbent with a benzene adsorption rate of 98.4% and a volatile alkane adsorption rate of 99.2%, showing significantly improved gas adsorption performance; the similar compatibility of the non-polar modifier is used to increase the adsorption-desorption function of the waste gas adsorbent. By adjusting the concentration of the modifier, the desorption rate of the waste gas adsorbent is 94%, and the adsorption capacity decays to 3% after 100 cycles, which has significantly improved cyclic adsorption performance.

[0011] To achieve the above object, the present invention provides the following technical solutions:

[0012] On one hand, the present invention provides a method for preparing a waste gas adsorbent for lubricating oil production, characterized in that: the waste gas adsorbent comprises a self-made ZIF-8 precursor, fluorinated graphene, a hydrophobic carbon dot HCDs solution, and an improver;

[0013] The preparation of the exhaust gas adsorbent comprises the following steps:

[0014] Dissolve imidazole in a solvent to prepare solution one, wherein the concentration of solution one is 10-40 mg / ml; dissolve zinc metal salt in a solvent to prepare solution two, wherein the concentration of solution two is 10-40 mg / ml; dissolve the fluorinated graphene in the HCDs solution to prepare solution three; slowly pour the solution one into the solution two to prepare a clear solution; transfer the clear solution to a 100 mL autoclave, react at 120° C. for 20 h, so that the metal salt and the organic ligand self-assemble to prepare a ZIF-8 precursor; slowly add the solution three to the ZIF-8 precursor, react at 120° C. for 5 h to prepare a MOF crystal; cool the MOF crystal to room temperature, centrifuge, wash the obtained solid with methanol several times, and dry it in a vacuum drying oven at 70° C. for 10 h to prepare a HFGO@ZIF-8-HCDs material;

[0015] The improver is dissolved in an ethanol solution to obtain an improver solution; the HFGO@ZIF-8-HCDs material is immersed in the improver solution, and stirred at 200 rpm for 30 minutes to obtain a treatment liquid; the treatment liquid is centrifuged, washed with methanol for 3 times, and vacuum dried at 70° C. for 2 hours to obtain an exhaust gas adsorbent;

[0016] The molar ratio of the zinc metal salt to the imidazole is 1:4-12;

[0017] The concentration multiple of the HCDs solution is 0.5-5 times;

[0018] The mass ratio of the ZIF-8 precursor to the fluorinated graphene is 1:0.05-0.15;

[0019] The mass ratio of the HFGO@ZIF-8-HCDs material to the improver is 1:0.05-0.2.

[0020] Preferably, the zinc metal salt is selected from zinc nitrate hexahydrate, zinc acetate and zinc chloride.

[0021] Preferably, the solvent is selected from dimethylformamide, methanol, water or a combination of two thereof.

[0022] Preferably, the imidazole is selected from 2-methylimidazole, 2-aminoimidazole, and 2-trifluoromethylimidazole.

[0023] Preferably, the preparation of the fluorinated graphene comprises the following steps:

[0024] The flake graphite and sodium nitrate were added to concentrated sulfuric acid (mass fraction of 98%), and after ultrasonic mixing for 10 minutes, the reaction solution was stirred at 100 rpm for 2 hours under ice bath conditions to obtain a reaction solution; the reaction solution was heated to 40°C, and the stirring reaction was continued for 0.5 hours, deionized water was added, and the temperature was continued to rise to 100°C. Under stirring conditions, 3 ml of 30 wt% hydrogen peroxide solution was slowly added, and a precipitate was obtained after standing and stratification; the precipitate was repeatedly washed with deionized water and centrifuged until the pH value of the upper clear liquid was neutral, and the reaction solution was placed in a vacuum drying oven at 70°C for drying to obtain graphene oxide;

[0025] The graphene oxide and deionized water are added into a beaker, and ultrasonic dispersion is performed for 20 minutes to obtain a graphene oxide dispersion liquid; a mixed solution of hydrofluoric acid and potassium permanganate is added into the graphene oxide dispersion liquid, and ultrasonic dispersion is performed for 30 minutes to obtain a mixed dispersion liquid; the mixed dispersion liquid is transferred into a hydrothermal reactor, and the hydrothermal temperature is 130° C., and the ultrasonic frequency is 15KHz, and the reaction is performed for 3 hours, and then the hydrothermal temperature is adjusted to 180° C., and the ultrasonic frequency is 35KHz, and the reaction is continued for 20 hours to obtain a reaction liquid; the reaction liquid is centrifuged, washed with deionized water until neutral, and dried in a vacuum drying oven at 70° C. to obtain fluorinated graphene.

[0026] Preferably, the mass of the potassium permanganate is 300mg-500mg.

[0027] Preferably, the preparation of the HCDs solution comprises the following steps:

[0028] L-ascorbic acid was added to a three-necked flask, and anhydrous ethanol was added. After ultrasonic treatment for 10 minutes, the mixture was refluxed at 80°C for 10 hours. Hexadecylamine was added and the mixture was refluxed at 80°C for 6 hours to obtain a red-brown solution to prepare the HCDs solution.

[0029] Preferably, the concentration multiple of the HCDs solution is 0.5-3 times; the preparation of the 1-fold concentration of the HCDs solution includes the following method:

[0030] 0.1 g of L-ascorbic acid was added to a three-necked flask, and anhydrous ethanol was added. After ultrasonic treatment for 10 min, the mixture was refluxed at 80° C. for 10 h. 0.18 g of hexadecylamine was added and the mixture was refluxed at 80° C. for 6 h to obtain a red-brown solution to prepare the HCDs solution.

[0031] Preferably, the improver is selected from one of divinylbenzene, styrene, terephthalic acid, trivinylbenzene and acrylic acid.

[0032] On the other hand, the present invention provides a lubricating oil production waste gas adsorbent, characterized in that: the lubricating oil production waste gas adsorbent comprises a ZIF-8 precursor, fluorinated graphene, a hydrophobic carbon dot (HCDs) solution, and an improver; the waste gas adsorbent is prepared by any one of the preparation methods described above; the T10% of the ZIF-8 precursor in the waste gas adsorbent is 428°C, and the T50% is 556°C; the average particle size of the ZIF-8 precursor in the waste gas adsorbent is 50nm, and the specific surface area is 1658m2 / g; the water contact angle of the HFGO@ZIF-8 precursor in the waste gas adsorbent is 110.8; the benzene adsorption rate of the waste gas adsorbent is 98.4%, and the alkane adsorption rate is 99.2%; the desorption rate of the waste gas adsorbent is 94%, and the adsorption capacity decays by 3% after 100 cycles.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention uses a solvent hydrothermal method to prepare ZIF-8MOF material, and uses ZIF-8 as a carrier skeleton material of a waste gas adsorbent. The yield of ZIF-8 is improved by controlling the molar ratio of zinc nitrate hexahydrate and 2-methylimidazole. Excessive dimethylimidazole will affect the crystal structure of ZIF-8, causing crystal deformation and decreased stability. Under high temperature, imidazole is rapidly decomposed by heat, destroying the crystal stability and reducing heat resistance. By using a solvent thermal method and controlling the molar ratio of zinc nitrate hexahydrate and 2-methylimidazole to be 1:8, the yield of the synthesized ZIF-8 skeleton material is the highest, T 10% 428℃, T 50% It is 556℃, showing significantly improved high temperature resistance.

[0035] 2. The present invention uses zinc nitrate hexahydrate as Zn 2+ ZIF-8 was synthesized by solvent thermal reaction in a pressure autoclave using a 2-methylimidazole solution. During the preparation process, it was found that the specific surface area decreased with the increase of pore size. 2+When dissolved in water, it will bind tightly to water molecules, thereby inhibiting their binding to organic ligands and greatly slowing down the nucleation rate, thus forming larger ZIF-8 particles. Zinc nitrate has a greater solubility, allowing a larger concentration of Zn in the solvent. 2+ The nucleation rate was increased by coordinating with deprotonated 2-methylimidazole molecules, and the resulting ZIF-8 particles were smaller in size. By changing the solvent type and controlling the source and molar ratio of the raw materials, the average particle size of the prepared ZIF-8 precursor was 50 nm and the specific surface area was 1658 m 2 / g, the adsorption capacity is enhanced.

[0036] 3. The present invention increases the hydrophobicity of the ZIF-8 precursor by changing the type of imidazole, and improves the hydrophobicity of the prepared HFGO@ZIF-8 material by adding fluorinated graphene. Due to the high electronegativity of fluorine atoms, adjacent fluorine atoms repel each other. At the same time, the low surface energy of fluorine atoms causes fluorine atoms to migrate to the surface of the material to form a hydrophobic structure. By adjusting the degree of fluorination in the synthesis of fluorinated graphene, the water contact angle of the prepared HFGO@ZIF-8 material is 110.8°, which has significantly improved hydrophobic properties.

[0037] 4. The present invention uses a solution made from hydrophobic carbon dots HCDs to dissolve fluorinated graphene, and by controlling the multiples of the concentration in the HCDs synthesis, explores the separation and adsorption capacity of the waste adsorbent for benzene series and volatile alkanes under different adsorption temperatures, humidity and gas concentrations. By utilizing the synergistic effect of fluorinated graphene and HCDs, the fluorinated graphene is stably loaded in the ZIF-8 precursor, and the non-polar groups on the surface of the adsorbent are enriched, thereby increasing the adsorption of the adsorbent to non-polar molecules. At the same time, the air humidity is controlled to avoid competitive adsorption of water and organic waste gas. By controlling the multiples of the HCDs solution concentration, the waste gas adsorbent obtained has a benzene adsorption rate of 98.4% and an alkane adsorption rate of 99.2%, showing a significantly improved production gas adsorption performance.

[0038] 5. The present invention uses a modifier, which partially occupies the pore size of the HFGO@ZIF-8-HCDs material. The compatibility of the non-polar modifier and the non-polar organic waste gas is used to increase the adsorption-desorption function of the waste gas adsorbent, so that the pores of the skeleton material have a cyclic adsorption effect. As the content of the modifier increases, the structural stability and adsorption capacity are affected. If the content of the modifier is too little, the effect of "dissolving" the organic waste gas cannot be fully exerted, which is not conducive to the desorption of the waste gas. By controlling the concentration of the modifier, the desorption rate of the waste gas adsorbent is 94%, and the adsorption capacity decays to 3% after 100 cycles, which has significantly improved the cyclic adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The XRD pattern of ZIF-8 prepared in Example 1-3;

[0040] Figure 2 The thermogravimetric curves of Examples 1-3 are shown in FIG. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] See also Figure 1 to Figure 2 The present invention provides a lubricating oil production waste gas adsorbent and a preparation method thereof, and the technical scheme is as follows:

[0043] Example 1

[0044] 2-Methylimidazole (8 mmol) was dissolved in 20 ml of methanol, and then a solution of zinc nitrate hexahydrate (1 mmol) dissolved in 10 ml of methanol was slowly poured into the above methanol solution of 2-methylimidazole, and the mixed solution gradually turned into a white flocculent precipitate, and then stirred at room temperature for 24 hours; after the reaction was completed, the mixed solution was centrifuged, and the obtained white solid was washed with anhydrous methanol (3×20 mL), and finally, the white solid was placed in a vacuum drying oven and dried at 70°C for 10 hours to obtain ZIF-8.

[0045] Example 2

[0046] 2-Methylimidazole (8 mmol) was dissolved in 5 ml of dimethylformamide to prepare solution 1; zinc nitrate hexahydrate (1 mmol) was dissolved in 1 ml of dimethylformamide to prepare solution 2; the solution 1 was slowly poured into the solution to prepare a clear solution; the clear solution was transferred to a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and reacted at 120°C for 20 h to allow the metal salt and the organic ligand to self-assemble to prepare MOF crystals; after the reaction, the MOF crystals were cooled to room temperature and centrifuged, and the obtained solid was washed with methanol several times and dried in a vacuum drying oven at 70°C for 10 h to prepare ZIF-8.

[0047] Example 3

[0048] 2-Methylimidazole (8 mmol), zinc nitrate hexahydrate (1 mmol) and 3 ml of tetrahydrofuran were placed in a ball mill at room temperature, and the mixture was reacted at 30 Hz / min for 5 hours at room temperature. After the reaction, a white solid was obtained by filtration, and the solid was washed with tetrahydrofuran and deionized water. The white solid was placed in a vacuum drying oven and dried at 70°C for 10 hours to obtain ZIF-8.

[0049] In order to determine whether the MOFs material was successfully synthesized, the ZIF-8 prepared above was subjected to XRD test and the results were recorded in Figure 1 In the figure, curves a, b, and c correspond to the ZIF-8 prepared in Example 1, Example 2, and Example 3, respectively.

[0050] Examples 4-11 refer to the preparation method of Examples 1-3, and the amounts of components are changed as shown in Table 1.

[0051] Table 1 Relationship between the preparation amount of Examples 1-11

[0052]

[0053] Example 12 Determination of heat resistance

[0054] Thermogravimetric analyzer, selected from TG209F3 of NETZSCH Scientific Instrument Trading (Shanghai) Co., Ltd. The ZIF-8 prepared in the above Examples 1-11 was tested under the conditions of N2 flow rate of 40 mL / min, heating rate of 10 °C / min, and heating range from room temperature to 700 °C, and T 10% 、T 50% . T 10% is the temperature corresponding to 10% mass loss, T 50% is the temperature corresponding to the mass loss of 50%. The test results are shown in Table 2. The thermogravimetric curves of some embodiments are shown in Figure 2 shown.

[0055] Table 2 Heat resistance of Examples 1-11

[0056]

[0057]

[0058] pass Figure 1 As a result, taking the sample obtained in Example 2 as an example (curve b), when the 2θ angles are 7.28°, 10.24°, 12.54°, 14.48°, 16.26°, 17.95°, 24.32° and 26.51°, they correspond to the crystal plane structure of ZIF-8, respectively, proving that the synthesized material is indeed ZIF-8, and the peak positions of curves a, b and c are all consistent, but the diffraction peak intensity is slightly different from curve b. Combined with the results in Table 1, it can be seen that different synthesis methods affect the yield of ZIF-8, showing that the peak intensity in the XRD results is inconsistent, and the yield of ZIF-8 obtained by solvent heat is higher, the crystal structure is doped with less impurity structure, and the high temperature resistance is better; Figure 2The TGA curve results show that at 25-150°C, the residual solvents such as dimethylformamide, water and methanol are removed, and the material quality loss is small; when the temperature rises to 400-600°C, the ZIF-8 skeleton structure begins to collapse, decomposes and loses weight, but the weight loss rate is stable, showing obvious high temperature resistance. When used as an adsorbent, it can also show high structural stability when used in a high temperature environment; It can be seen from the results of Examples 1-3 that different synthesis methods will affect the ZIF-8 yield. The ZIF-8 crystalline MOF structure can be obtained by using the room temperature synthesis method, but compared with the solvent hydrothermal method, the reaction yield is not improved by extending the reaction time. At room temperature, due to the low thermal diffusion effect, zinc nitrate hexahydrate and 2-methylimidazole cannot Effective combination; ZIF-8 is obtained under mechanical stirring conditions using a grinder. The material has a poor crystal structure and a high impurity content. When used under high temperature conditions, due to the influence of impurities, the high temperature resistance is reduced and the application conditions are limited; the results of Examples 4-11 show that with the increase of the dimethylimidazole content, the synthesis yield of ZIF-8 shows a trend of first increasing and then decreasing. Excessive dimethylimidazole content will lead to the rapid formation of ZIF-8. When the maximum reaction rate is reached, excessive dimethylimidazole will affect the ZIF-8 crystal structure, resulting in crystal deformation, decreased stability, and reduced yield. The residual dimethylimidazole occupies the ZIF-8 crystal pores. Under high temperature, imidazole is rapidly decomposed by heat, destroying the crystal stability and reducing heat resistance. From the results of Table 2, it can be seen that when the solvent hydrothermal method is used and the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is maintained at 1:8, the synthesized ZIF-8 yield is the highest, T 10% 428℃, T 50% It is 556℃, showing significantly improved high temperature resistance.

[0059] Example 12

[0060] 6.4 g 2-methylimidazole (80 mmol) was dissolved in 200 ml dimethylformamide to prepare solution 1, and the concentration of 2-methylimidazole was 30 mg / ml; 2.9 g zinc nitrate hexahydrate (10 mmol) was dissolved in 100 ml dimethylformamide to prepare solution 2, and the concentration of zinc nitrate hexahydrate was 30 mg / ml; the solution 1 was slowly poured into the solution to prepare a clear solution; the clear solution was transferred to a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and reacted at 120° C. for 20 h to allow the metal salt and the organic ligand to self-assemble to prepare MOF crystals; after the reaction, the MOF crystals were cooled to room temperature and centrifuged, and the obtained solid was washed with methanol several times and dried in a vacuum drying oven at 70° C. for 10 h to prepare ZIF-8.

[0061] Examples 13-22 refer to the preparation methods and parameter conditions of Example 2, with the differences shown in Table 3.

[0062] Table 3 Variation of preparation conditions of Examples 12-23

[0063]

[0064] Example 24 Specific surface area determination

[0065] BET specific surface area and pore volume are calculated by 2 The adsorption-desorption isotherm curve analysis showed that the ZIF-8 precursors prepared in Examples 12-22 were measured on a JW-ZQ200C specific surface area adsorption instrument using a 77K N2 static adsorption method. The vacuum degree of the sample chamber was P / P 0 = in the range of 0-1, where P 0 Before the test, the sample material prepared above was vacuum dried at 200°C for 12 hours, and the specific surface area of ​​the sample was calculated using the multi-point BET method. The results are shown in Table 4.

[0066] Table 4 Specific surface area determination of Examples 12-22

[0067]

[0068]

[0069] From the results in Table 4, we can see that with the increase of the average particle size of ZIF-8 precursor, the specific surface area and pore volume decrease to a certain extent. Therefore, the factors affecting the specific surface area of ​​ZIF-8 precursor are mainly Zn 2+ Source, raw material concentration, raw material molar ratio and solvent type. Since the mesopores and macropores mainly act as channels, they can reduce the transport resistance of the adsorbate molecules from the adsorption interface to the micropores. The micropore structure determines the adsorption capacity of the material. The larger the number of micropores and the larger the specific surface area, the stronger the adsorption effect on molecules with smaller diameters. The results of Examples 12-14 show that the ZIF-8 precursor prepared by zinc nitrate hexahydrate has a smaller average pore size and a larger specific surface area; compared with zinc acetate and zinc chloride, zinc nitrate has a greater solubility, allowing a higher concentration of Zn in the solvent. 2+ and deprotonated 2-methylimidazole molecules to increase the nucleation rate, and the resulting ZIF-8 particles are smaller in size; By comparing the results of Examples 16-20, it can be seen that when Zn 2+When the concentration of 2-methylimidazole is high or when 2-methylimidazole is excessive, the rate of the initial nucleation stage can be increased. Rapid nucleation will result in the generation of a large number of nuclei. When these nuclei grow into smaller single particles, they will stop growing due to the decrease in supersaturation, and eventually generate ZIF-8 particles with smaller particle size, increasing the specific surface area of ​​the material. However, excessive 2-methylimidazole will affect the supersaturation of the reaction, affect the crystal structure of ZIF-8, and further affect other properties. It can be seen from the results of Examples 21-23 that the particle size of ZIF-8 particles prepared using water as a solvent becomes larger, and the specific surface area is significantly reduced. Due to Zn 2+ When dissolved in water, it will bind tightly to water molecules, thereby inhibiting their binding with organic ligands and greatly slowing down the nucleation rate, thus forming larger ZIF-8 particles, resulting in a decrease in specific surface area, a decrease in micropore volume, and a weakened adsorption capacity. 2+ The source was dimethylformamide as the reaction solvent, the raw material concentration was 30 mg / ml, and the average particle size of the prepared ZIF-8 precursor was 50 nm and the specific surface area was 1658 m 2 / g, the adsorption capacity is enhanced.

[0070] Embodiment 25

[0071] 2 g of flake graphite and 1 g of sodium nitrate were added to a beaker containing 50 ml of concentrated sulfuric acid (mass fraction of 98%), and mixed by ultrasonication for 10 min. The mixture was stirred at 100 rpm for 2 h in an ice bath to obtain a reaction solution. The reaction solution was heated to 40° C., and the stirring reaction was continued for 0.5 h. 100 ml of deionized water was added, and the temperature was continued to rise to 100° C. Under stirring conditions, 3 ml of 30 wt% hydrogen peroxide solution was slowly added. After standing for stratification, a precipitate was obtained. The precipitate was repeatedly washed with deionized water and centrifuged until the pH value of the supernatant was neutral, and the mixture was dried in a vacuum drying oven at 70° C. to obtain graphene oxide.

[0072] 100 mg of the graphene oxide and 50 ml of deionized water are added to a beaker, and ultrasonic dispersion is performed at an ultrasonic frequency of 50 kHz and an ultrasonic intensity of 1 W / cm2 for 20 minutes to obtain a graphene oxide dispersion; 5 ml of a mixed solution of 40 wt% hydrofluoric acid and 300 mg of potassium permanganate is added to the graphene oxide dispersion, and ultrasonic dispersion is performed for 30 minutes to obtain a mixed dispersion; the mixed dispersion is transferred to a hydrothermal reactor, and the hydrothermal temperature is 130° C. and the ultrasonic frequency is 15 KHz, and the reaction is performed for 3 hours, then the hydrothermal temperature is adjusted to 180° C. and the ultrasonic frequency is 35 KHz, and the reaction is continued for 20 hours to obtain a reaction solution; the reaction solution is centrifuged, washed with deionized water until neutral, and dried in a vacuum drying oven at 70° C. to obtain fluorinated graphene.

[0073] 6.4 g of methylimidazole (80 mmol) was dissolved in 200 ml of dimethylformamide to prepare solution 1, and the concentration of methylimidazole was 30 mg / ml; 2.9 g of zinc nitrate hexahydrate (10 mmol) was dissolved in 100 ml of dimethylformamide to prepare solution 2, and the concentration of zinc nitrate hexahydrate was 30 mg / ml; the fluorinated graphene was dissolved in dimethylformamide to prepare solution 3; the solution 1 was slowly poured into the solution to prepare a clear solution; the clear solution was transferred to a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and reacted at 120° C. for 20 h to allow the metal salt and the organic ligand to self-assemble to prepare a reaction system; the solution 3 was slowly added to the reaction system, and reacted at 120° C. for 5 h to prepare MOF crystals; the MOF crystals were cooled to room temperature, centrifuged, and the obtained solids were washed with methanol several times, and dried at 70° C. in a vacuum drying oven for 10 h to prepare HFGO@ZIF-8 materials.

[0074] Examples 26-33 refer to the preparation method and parameter conditions of Example 25, and the differences are shown in Table 5.

[0075] Comparative Example 1 refers to the preparation method and parameter conditions of Example 25, except that no fluorinated graphene is added.

[0076] Comparative Example 2 refers to the preparation method and parameter conditions of Example 25, except that potassium permanganate is not added during the preparation of fluorinated graphene.

[0077] Example 34 Water contact angle test

[0078] The water contact angle was tested using a DSA100S contact angle meter from KRUSS, Germany. Before the test, the materials obtained in Examples 26-33 and Comparative Examples 1-2 were pressed into sheets and samples were prepared. During the sample preparation, a pressure of 4 MPa was maintained for 20 seconds. The results are shown in Table 5.

[0079] Table 5 Water contact angle test of Examples 25-33 Comparative Examples 1-2

[0080]

[0081]

[0082] It can be seen from the results in Table 5 that the ZIF-8 precursor obtained in Comparative Example 1 without adding fluorinated graphene has obvious hydrophilicity, and the ZIF-8 precursor has high hydrophilicity due to the metal ions in the skeleton structure and the polar covalent effect; HFGO@ZIF-8 material is obtained by adding fluorinated graphene in Comparative Example 2. Due to the introduction of surface fluorine atoms, the hydrophobicity of the material is increased, but due to the low degree of fluorination and low fluorine atom content, the hydrophobicity is poor; It can be seen from the results of Examples 25 and 28-29 that with the increase of the amount of potassium permanganate, the fluorination degree of fluorinated graphene decreases. Due to the strong oxidizing effect of potassium permanganate, the degree of graphene oxidation is increased, the fluorine atom substitution in the molecule is reduced, and the increase of oxygen-containing functional groups provides hydrogen bonding force, which further reduces the hydrophobicity of the material; 25-27 results show that 2-trifluoromethylimidazole is used as a raw material for preparing ZIF-8 to reduce the presence of polar groups in the skeleton structure, avoid the generation of covalent effects and improve hydrophilicity; Example 25, Example 30-33 results show that with the increase in the amount of fluorinated graphene, the water contact angle of HFGO@ZIF-8 material gradually increases. Due to the large electronegativity of fluorine atoms, the electron cloud density around the atoms is densely distributed, resulting in mutual repulsion between adjacent fluorine atoms. At the same time, the low surface energy of fluorine atoms causes fluorine atoms to migrate to the interface formed by the material and the air, forming a hydrophobic barrier on the surface of the material, further improving the hydrophobic performance, but excessive fluorinated graphene can cause crystal defects and pore blockage, further affecting the adsorption performance of HFGO@ZIF-8 materials. Comprehensive Table 1 results show that the water contact angle of HFGO@ZIF-8 material prepared by using 2-trifluoromethylimidazole as imidazole raw material and 300mg potassium permanganate is 110.8°, which has significantly improved hydrophobic performance.

[0083] Embodiment 35

[0084] Preparation of fluorinated graphene: refer to the preparation method and parameter conditions of Example 27;

[0085] 0.05 g of L-ascorbic acid was weighed into a three-necked flask, and 100 mL of anhydrous ethanol was added. After ultrasonication for 10 min, the mixture was refluxed at 80 °C for 10 h. 0.09 g of hexadecylamine was added and the mixture was refluxed at 80 °C for 6 h to obtain a red-brown solution to prepare the HCDs solution.

[0086] 2-Trifluoromethylimidazole (80 mmol) was dissolved in 200 ml of dimethylformamide to obtain solution 1, and the concentration of methylimidazole was 30 mg / ml; zinc nitrate hexahydrate (10 mmol) was dissolved in 100 ml of dimethylformamide to obtain solution 2, and the concentration of zinc nitrate hexahydrate was 30 mg / ml; 1 g of fluorinated graphene was dissolved in the HCDs solution to obtain solution 3; solution 1 was slowly poured into the solution to obtain a clear solution; the clear solution was transferred to a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and reacted at 120° C. for 20 h to allow the metal salt and the organic ligand to self-assemble to obtain a reaction system; solution 3 was slowly added to the reaction system, and reacted at 120° C. for 5 h to obtain MOF crystals; the MOF crystals were cooled to room temperature, centrifuged, and the obtained solid was washed with methanol several times, and dried at 70° C. in a vacuum drying oven for 10 h to obtain HFGO@ZIF-8-HCDs material;

[0087] 0.12 g of divinylbenzene was dissolved in an ethanol solution to obtain a divinylbenzene solution; 1 g of the HFGO@ZIF-8-HCDs material was immersed in the divinylbenzene solution and stirred at 200 rpm for 30 min to obtain a treatment liquid; the treatment liquid was centrifuged, washed with methanol for 3 times, and vacuum dried at 70° C. for 2 h to obtain a waste gas adsorbent.

[0088] Examples 36-49 refer to the preparation method and parameter conditions of Example 35, and the differences are shown in Table 6.

[0089] Comparative Example 3 refers to the preparation method and parameter conditions of Example 35, but does not use HCDs to dissolve the fluorinated graphene.

[0090] Example 50 Adsorption performance test

[0091] The waste gas adsorbent prepared in Examples 35-49 and Comparative Example 3 was loaded onto a fixed adsorption bed, with benzene and volatile alkanes, the main components of lubricating oil production waste gas, as the adsorption gas, the carrier gas was air, the concentration of the adsorbed gas in the sample gas was 400-700 ppm, the temperature of the adsorption process was controlled at 25-50°C, the air velocity was 2500h-1, the parameter changes were shown in Table 6, and the test results were shown in Table 7.

[0092] Table 6 Parameters and conditions of Examples 35-49 and Comparative Example 3

[0093] Example Adsorption temperature / ℃ <![CDATA[Adsorbed gas concentration / mg / m 3 > Adsorption humidity / % HCDs solution concentration / times Embodiment 35 25 400ppm 60% 0.5 Embodiment 36 25 400ppm 60% 1 Embodiment 37 25 400ppm 60% 1.5 Embodiment 38 25 400ppm 60% 2 Embodiment 39 25 400ppm 60% 3 Embodiment 40 30 400ppm 60% 2 Embodiment 41 40 400ppm 60% 2 Embodiment 42 50 400ppm 60% 2 Embodiment 43 25 500ppm 60% 2 Embodiment 44 25 600ppm 60% 2 Embodiment 45 25 700ppm 60% 2 Embodiment 46 25 400ppm 40% 2 Embodiment 47 25 400ppm 50% 2 Embodiment 48 25 400ppm 80% 2 Embodiment 49 25 400ppm 90% 2

[0094] Table 7 Adsorption performance test of Examples 35-49 and Comparative Example 3

[0095]

[0096]

[0097] From the results in Table 7, it can be seen that the adsorption rate and adsorption capacity of organic gases in Comparative Example 3 without adding HCDs are significantly lower than those in Examples 35-49. The data of Examples 35-39 show that with the increase of the concentration of the HCDs solution, the adsorption rate and adsorption capacity of benzene and alkane gases first increase and then decrease. Since HCDs synergizes with fluorinated graphene after addition to produce more micropores, it is beneficial to the adsorption of benzene molecules and alkane non-polar molecules. With the increase of the addition amount of HCDs, the adsorption amount of the composite adsorbent for non-polar molecules shows a trend of first increasing and then decreasing. Since the HCDs content is too high, it will cause crystal defects, thereby reducing the specific surface area and pore volume, and reducing the adsorption of benzene and alkane non-polar gases by the exhaust gas adsorbent; From the results of Examples 35 and 40-42, it can be seen that with the increase of the adsorption temperature, the adsorption rate slowly increases and the adsorption amount increases significantly. Especially in the process of benzene adsorption, since the interaction between molecules becomes more intense with the increase of temperature, the separation can be reduced. The difficulty of the molecules entering the narrow micropores of the adsorbent is increased, and the adsorption amount is increased; Examples 43-45 and Example 35 show that as the adsorption concentration increases, the adsorption rate of the adsorbent remains unchanged. Due to the limited adsorption capacity of the adsorbent, the increase in concentration can reach the maximum adsorption rate in a relatively short time, but as time goes on, the adsorption capacity gradually increases. Due to the synergistic effect of fluorinated graphene and HCDs, the non-polar groups on the surface of the adsorbent are enriched, which increases the adsorption of non-polar molecules; The results of Examples 35 and 46-49 show that as the humidity of the system increases, the adsorption first increases and then decreases. When the humidity of the system is too high, the water molecules in the air are competitively adsorbed in the material, and the water directly occupies the adsorption sites, which reduces the adsorption capacity of the adsorbent for benzene and alkane molecules. The synergistic effect of fluorinated graphene and hydrophobic carbon dots HCDs is used in the material to improve the hydrophobicity inside the skeleton material. However, water molecules will react with the polar groups on the surface of the adsorbent, affecting the entry of non-polar molecules into the adsorbent and reducing the continuous adsorption capacity of the adsorbent. From the results in Table 7, it can be seen that the waste gas adsorbent formed by dissolving fluorinated graphene in 2 times HCDs solution and compounding it with ZIF-8 has a benzene adsorption rate of 98.4% and an alkane adsorption rate of 99.2%, showing a significantly improved non-polar gas adsorption performance.

[0098] Examples 51-59 refer to the preparation method and parameter conditions of Example 38, and the differences are shown in Table 8.

[0099] Comparative Example 4 refers to the preparation method and parameter conditions of Example 38, except that no improver is used.

[0100] Example 60 Cyclic Adsorption Performance Test

[0101] The waste gas adsorbents prepared in Examples 51-59 and Comparative Example 4 were loaded onto a fixed adsorption bed, and the main components of the waste gas from lubricating oil production, benzene series and volatile alkanes, were used as adsorption gases. The carrier gas was air, and the concentration of the adsorbed gas in the sample gas was 500 ppm. The temperature during the adsorption process was controlled at 40°C, and the air velocity was 1500 h -1 The desorption process temperature is room temperature, the desorption medium is air, and the air velocity is 1500h -1 , the difference method is used to calculate the static adsorption capacity of the adsorbent for organic matter. The calculation formula for the static adsorption capacity is:

[0102] Adsorption capacity (%) = M 吸附后 -M 吸附前 / M 吸附前 ×100%

[0103] Among them, M 吸附后 Indicates the mass of exhaust gas adsorbent after static adsorption, M 吸附前 The adsorption capacity decay rate was calculated after 100 cycles. The results are shown in Table 8.

[0104] Table 8 Cyclic adsorption performance measurement of Examples 51-59 and Comparative Example 4

[0105] Example Improver Type Improver dosage / % Desorption rate / % Adsorption capacity decay / % Embodiment 51 Divinylbenzene 12% 93% 5% Embodiment 52 Styrene 12% 90% 6% Embodiment 53 4-Benzoic acid 12% 88% 10% Embodiment 54 Trivinylbenzene 12% 94% 3% Embodiment 55 acrylic acid 12% 81% 25% Embodiment 56 Trivinylbenzene 5% 86% 9% Embodiment 57 Trivinylbenzene 8% 90% 5% Embodiment 58 Trivinylbenzene 15% 88% 6% Embodiment 59 Trivinylbenzene 20% 82% 12% Comparative Example 4 / / 72% 30%

[0106] It can be seen from the results in Table 8 that the desorption rate of the HFGO@ZIF-8-HCDs material obtained by the improvement treatment without using the improver divinylbenzene in Comparative Example 4 is significantly lower than that of Examples 51-59, and the adsorption capacity decay after 100 times is higher than that of Examples 51-59, showing significantly poor cyclic adsorption performance; It can be seen from the results of Examples 51-55 that the use of polar improvers has poor compatibility with non-polar organic gases, and the desorption rate gradually decreases during repeated adsorption. After multiple adsorption-desorption, the interior of the material is occupied by the desorbed organic gas, affecting the recyclability; The non-polar molecule trivinylbenzene is loaded on the HFGO@ZIF-8-HCDs material, and the adsorption effect of the pores of the skeleton material on the organic waste gas and the "dissolution" effect of trivinylbenzene on the organic waste gas are fully utilized. The combination of the two synergistically improves the waste gas adsorption effect. During desorption, due to the presence of mesopores and macropores in the ZIF-8 precursor structure, the desorption of organic waste gas is easier, thereby improving the desorption efficiency. Combined with the results in Tables 6 and 7, it can be seen that trivinylbenzene The addition of benzene has a good effect on adsorption and desorption, and the reinforcement of the carrier matrix by trivinylbenzene greatly reduces the attenuation of the adsorption capacity of the adsorbent, which is beneficial to improving the service life of the adsorbent; when the modifier is not loaded, the structural strength of HFGO@ZIF-8-HCDs is weakened, and it cannot adapt to multiple cycles of adsorption-desorption process, and the structure is prone to collapse; It can be seen from the results of Examples 51 and 57-59 that the change in the trivinylbenzene content in the waste gas adsorbent will affect the adsorption effect. As the trivinylbenzene content increases, the desorption rate shows an increase first and then a decrease, while the adsorption capacity attenuation shows a trend of decreasing and then increasing. Excessive trivinylbenzene loading will occupy the ZIF-8 pore structure, causing the adsorption effect to weaken, and due to excessive trivinylbenzene occupying the pores, the overall strength of the structure decreases, the structure is prone to collapse, and the adsorption capacity is affected; if the trivinylbenzene loading is too little, it cannot play its role of "dissolving" organic waste gas, and is not conducive to the desorption of organic waste gas from the rich pore system, so the desorption effect is poor. From the results in Table 8, it can be seen that when trivinylbenzene with a concentration of 12% is used as the improver, the desorption rate of the exhaust gas adsorbent is 94%, and the adsorption capacity decays by 3% after 100 cycles, which has significantly improved cyclic adsorption performance.

[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a waste gas adsorbent for lubricating oil production, characterized in that: The exhaust gas adsorbent comprises a self-made ZIF-8 precursor, fluorinated graphene, a hydrophobic carbon dot HCDs solution, and an improver; The preparation of the exhaust gas adsorbent comprises the following steps: Dissolving 2-trifluoromethylimidazole in dimethylformamide to prepare solution 1, wherein the concentration of solution 1 is 30 mg / ml; dissolving zinc nitrate hexahydrate in a solvent to prepare solution 2, wherein the concentration of solution 2 is 30 mg / ml; dissolving the fluorinated graphene in the HCDs solution to prepare solution 3; slowly pouring the solution 1 into the solution 2 to prepare a clear solution; transferring the clear solution to a 100 mL autoclave, reacting at 120° C. for 20 h, allowing the metal salt and the organic ligand to self-assemble to prepare the ZIF-8 material; The solution three was slowly added to the ZIF-8 precursor, and the reaction was carried out at 120° C. for 5 h to obtain MOF crystals; the MOF crystals were cooled to room temperature, centrifuged, and the obtained solid was washed with methanol for several times, and dried in a vacuum drying oven at 70° C. for 10 h to obtain HFGO@ZIF-8-HCDs material; The improver is dissolved in an ethanol solution to obtain an improver solution; the HFGO@ZIF-8-HCDs material is immersed in the improver solution, and stirred at 200 rpm for 30 minutes to obtain a treatment liquid; the treatment liquid is centrifuged, washed with methanol for 3 times, and vacuum dried at 70° C. for 2 hours to obtain an exhaust gas adsorbent; The molar ratio of the zinc nitrate hexahydrate to the 2-trifluoromethylimidazole is 1:8; The concentration multiple of the HCDs solution is 0.5-3 times; The preparation of the 1-fold concentration of the HCDs solution includes the following method: 0.1 g of L-ascorbic acid was added to a three-necked flask, and anhydrous ethanol was added. After ultrasonic treatment for 10 min, the mixture was refluxed at 80°C for 10 h. 0.18 g of hexadecylamine was added and the mixture was refluxed at 80°C for 6 h to obtain a reddish brown solution to prepare the HCDs solution. The mass ratio of the ZIF-8 precursor to the fluorinated graphene is 1:0.05-0.15; The mass ratio of the HFGO@ZIF-8-HCDs material to the improver is 1:0.05-0.2; The improver is selected from one of divinylbenzene, styrene, terephthalic acid, trivinylbenzene and acrylic acid; The preparation of the fluorinated graphene comprises the following steps: The flake graphite and sodium nitrate were added to concentrated sulfuric acid (mass fraction of 98%), and after ultrasonic mixing for 10 minutes, the reaction solution was stirred at 100 rpm for 2 hours under ice bath conditions to obtain a reaction solution; the reaction solution was heated to 40°C, and the stirring reaction was continued for 0.5 hours, deionized water was added, and the temperature was continued to rise to 100°C. Under stirring conditions, 3 ml of 30 wt% hydrogen peroxide solution was slowly added, and a precipitate was obtained after standing and stratification; the precipitate was repeatedly washed with deionized water and centrifuged until the pH value of the upper clear liquid was neutral, and the reaction solution was placed in a vacuum drying oven at 70°C for drying to obtain graphene oxide; The graphene oxide and deionized water are added into a beaker, and ultrasonically dispersed for 20 minutes to obtain a graphene oxide dispersion; a mixed solution of hydrofluoric acid and potassium permanganate is added into the graphene oxide dispersion, and ultrasonically dispersed for 30 minutes to obtain a mixed dispersion; the mixed dispersion is transferred into a hydrothermal reactor, and reacted for 3 hours under the conditions of a hydrothermal temperature of 130° C. and an ultrasonic frequency of 15 KHz, and then the hydrothermal temperature is adjusted to 180° C. and the ultrasonic frequency is 35 KHz, and the reaction is continued for 20 hours to obtain a reaction system; the reaction system is centrifuged, washed with deionized water until neutral, and dried in a vacuum drying oven at 70° C. to obtain fluorinated graphene; the mass of the potassium permanganate is 300 mg-500 mg.

2. A lubricating oil production waste gas adsorbent, characterized in that: The lubricating oil production waste gas adsorbent comprises a homemade ZIF-8 precursor, fluorinated graphene, a hydrophobic carbon dot HCDs solution, and an improver; the waste gas adsorbent is prepared by the preparation method described in claim 1.

Citation Information

Patent Citations

  • A kind of preparation method of hydrophobic activated carbon modified material

    CN104437444B

  • Hydrophobic activated carbon adsorbent for treating high-humidity VOCs and preparation method of hydrophobic activated carbon adsorbent

    CN111330543A